Rancang Bangun Prototype Sistem Peringatan Dini Banjir Berbasis Arduino dengan Komunikasi Wireless nRF - Ulfa Sari; Muhammad Anwar (MASALIQ, 2025)
Flooding is a frequent natural disaster in Indonesia, causing serious impacts such as loss of life, environmental damage, and economic losses. Limited access to fast and easily understood information often leaves communities unprepared to face it. This study aims to design and develop a prototype of a flood early warning system based on an Arduino microcontroller with wireless communication using the nRF24L01 module. The method used was the Waterfall model, consisting of analysis, design, implementation, testing, and maintenance stages. The system comprises a transmitter unit equipped with an ultrasonic sensor and a water level sensor to monitor water height, and a receiver unit that displays information via an LCD, provides visual alerts through indicator LEDs, and issues audio warnings using a DFPlayer Mini and speaker. Testing was conducted to measure sensor accuracy and system responsiveness in simulated flood conditions. The results show that the prototype can detect water levels with three status categories: Safe (>10 cm), Alert (>20 cm), and Emergency (>30 cm or high water level). Device-to-device communication was effective at distances of up to approximately 150 meters.